Knowledge as a Critical Resource in Innovation among Small Furniture Companies in Indonesia: An Exploration - Geenhuizen, Marina van; Indarti, Nurul (Gadjah Mada International Journal of Business, 2005)
The furniture industry makes a significant contribution to the Indonesian economy but is exposed to an intensifying competitive environment and to emerging shortages of raw material. These circumstances have prompted small furniture manufacturers in the district of Jepara to undertake several types of innovation. It appears that of all first ranked innovations, product innovation is the largest category. In the overall pattern of innovations, market innovation and logistics innovation are also important, a situation that can be explained by the typical character and current circumstances of the furniture industry in this area. The innovation process concerned mainly relies on traditional knowledge sources, namely in-house learning-by-doing and experimentation, and buyers (customers). However, the manufacturers show willingness to use other knowledge sources in the near future, particularly more formal and globally oriented ones, such as exhibitions, research institutions, and the Internet. What tends to hamper such progress is that the manufacturersâ capability to access these knowledge sources is limited by financial obstacles and to a smaller extent by complexity and language obstacles. The paper concludes with a few policy recommendations and potential directions of future research. One of the policy recommendations aims at a combination of the traditional way of knowledge generation through in-house learning-by-doing and experimentation with knowledge from modern and formal sources.